Management of follicular thyroid carcinoma - Haruhiko Yamazaki; Kiminori Sugino; Ryohei Katoh; Kenichi Matsuzu; Wataru Kitagawa; Mitsuji Nagahama; Aya Saito; Koichi Ito (European Thyroid Journal)
Follicular thyroid carcinoma (FTC) is the second most common histological type of thyroid carcinoma. This review aims to summarize the available evidence and guidelines and provide an updated consensus regarding the management of FTC. The cytoarchitectural features of FTC are similar to those of follicular adenoma (FA), and it is difficult to preoperatively distinguish between FA and FTC. For nodules with Bethesda class III–V cytology, molecular test results (if available) should be considered before the operation. However, it should be noted that molecular tests are not available in all countries. The goals of initial surgical therapy for patients with FTC are to improve overall and disease-specific survival, reduce the risk of persistent/recurrent disease and associated morbidity, and permit accurate disease staging and risk stratification while minimizing treatment-related morbidity and unnecessary therapy. Previous studies have reported some prognostic factors such as distant metastasis, age, tumor size, vascular invasion, TERT promoter mutation, and histological subtype. In particular, the degree of vascular invasion is becoming increasingly important. Evaluating these prognostic factors is essential for prognostic prediction and precise management of patients with FTC. Recurrence and distant metastasis of FTC are treated with radioactive iodine (RAI). However, some FTCs become refractory to RAI. Multi-tyrosine kinase inhibitors such as sorafenib and lenvatinib are utilized for treating RAI-refractory FTCs. In addition, given that renin–angiotensin system (RAS) is the most common driver gene for FTC, it is also important to develop RAS inhibitors.